ICT in Early Childhood Education. (Journal of Parents and Teachers, 2014)
This article continues to present ideas for integrating ICT in the classroom of Early Childhood Education. Therefore, a detailed resource catalog and a didactic unit on the subject of winter that includes these new technologies are offered.
Keywords: ICT; resources; Childhood Education; didactic unit.